2006
DOI: 10.2147/tcrm.2006.2.2.219
|View full text |Cite
|
Sign up to set email alerts
|

Cost-benefit analysis of influenza vaccination in a public healthcare unit

Abstract: Objective Estimate the costs and benefits of influenza vaccination in a group of employees of an Italian District Health Authority, Unità Locale Socio Sanitaria (ULSS), to define a scheme of an economic evaluation to be used for other vaccination strategies. Design In an observational study conducted from December 2002 to April 2003, 107 ULSS employees, voluntarily vaccinated, were compared with 107 nonvaccinated ULSS employees matched for age, sex, and job category. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 37 publications
0
55
0
Order By: Relevance
“…Only 15 of the 34 studies (44%) met more than 50% of the quality criteria (16, 18, 30, 33, 35-37, 39, 40, 44, 46, 49), and of these, 3 met greater than 75% of the criteria (30,33,36). Six of the economic evaluations were based on data from randomized controlled trials (16,17,27,30,36,46), 16 from a controlled before-and-after design (20, 22, 24, 29, 31-33, 35, 38, 40-45, 47), seven from a uncontrolled before-and-after design (18,19,23,26,28,48,49), four from case-controls (25,34,37,39), and one from a historical cohort (21).…”
Section: Methodological Quality Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Only 15 of the 34 studies (44%) met more than 50% of the quality criteria (16, 18, 30, 33, 35-37, 39, 40, 44, 46, 49), and of these, 3 met greater than 75% of the criteria (30,33,36). Six of the economic evaluations were based on data from randomized controlled trials (16,17,27,30,36,46), 16 from a controlled before-and-after design (20, 22, 24, 29, 31-33, 35, 38, 40-45, 47), seven from a uncontrolled before-and-after design (18,19,23,26,28,48,49), four from case-controls (25,34,37,39), and one from a historical cohort (21).…”
Section: Methodological Quality Assessmentmentioning
confidence: 99%
“…No included study performed a CUA. With respect to expressing the efficiency of a given intervention compared to its alternative, 65% of the financial appraisals (16, 17, 21-23, 26, 27, 29-31, 33, 34, 36-40, 43, 44, 46-48) reported the difference between monetary benefits and program costs as net savings or benefits, 32% (21,24,28,32,33,35,38,42,45,48,49) provided a benefit-to-cost ratio, 21% (18,19,27,30,38,41,45) reported the return-on-investment (ROI), 9% (20,22,26) calculated a payback period, and 6% (26, 28) noted an internal rate of return. Note that the total percentage is greater than 100% because ten studies reported two expressions each (21, 22, 26-28, 30, 33, 38, 45, 48).Twenty-eight of the studies reported cost savings or monetary benefits in favor of the intervention (16, 17, 19-22, 24, 26-31, 33-36, 38-46, 48, 49); three reported negative savings (25,37,47); two reported both negative and positive monetary benefits (18,23); and one reported both a costneutral and positive situation (32).…”
Section: Methodological Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In defining the costs of a vaccination program we adopt the approach of studies in the field of medical management (see [9], [10], [11]) and split these costs into two categories: medical and non-medical costs. Medical costs include vaccine costs, costs of service by nurses and physicians (calculated as the average service time multiplied by the average salary of nurses and doctors [9], [12]), as well as costs associated with possible vaccine shortage, which reflect the costs of additional hospitalization and outpatient services that clinics must provide as a direct result of vaccine shortage. Non-medical costs include transportation, delivery and inventory holding costs incurred by clinics and distribution centers.…”
Section: Literature Reviewmentioning
confidence: 99%